Pengaruh Gaya Hidup dan Kelompok Referensi Terhadap Keputusan Pembelian pada Produk MS Glow di Kota Malang - Marda Mellinia Islami; Achmad Zaini (Master Manajemen, 2025)
This research is a quantitative descriptive study with lifestyle and reference groups as independent variables and purchasing decisions as dependent variables. The data collection method used is a questionnaire with a purposive sampling technique to 100 respondents aged 20-37 in Malang who use MS Glow products. The data analysis technique used multiple linear regression and hypothesis testing. The multiple linear regression results show the equation of Y=19.639 + 0.718 X1 + 0. 94 X2 + e. The results of the t-test show that both lifestyle and reference group have a partial effect on purchasing decisions. And has a standard beta coefficient of 0.640 for lifestyle and 0,204 for reference group. The results of the F test show that lifestyle and reference groups have a simultaneous effect on purchasing decisions. The value of a Adjusted R Square (R²) is 0.633. The influence of lifestyle and reference groups on purchasing decisions of MS Glow products is 63.3%, while 36.7% is influenced by other factors not discussed in this study. Based on the research, it can be concluded that lifestyle and reference groups affect purchasing decisions of MS Glow products in Malang City. It is hoped that MS Glow can reach a wider community environment so that it can be accepted by all groups such as parents, not only teenagers to fulfill consumer lifestyles Besides, it is also hoped that MS Glow maintains the influence of reference groups to attract consumers to buy MS Glow products in Malang.